Safety assessment of enterocin-producing Enterococcus strains isolated from sheep and goat colostrum - Geniş, Burak; Öztürk, Hüseyin; Özden Tuncer, Banu; Tuncer, Yasin (BMC microbiology, 2024)
Background This study investigates the safety evaluation of enterocin-producing 11 E. mundtii and two E. faecium strains previously isolated from small livestock colostrums. Enterococcus species do not possess Generally Recognized as Safe (GRAS) status. Hence, it is critical to scrutinize enterococci’s antibiotic resistance, virulence characteristics, and biogenic amine production capabilities in order to assess their safety before using them as starter or adjunct cultures. Results Enterococcus strains showed susceptibility to medically significant antibiotics. Multiple-drug resistance (MDR) was found in only E. faecium HC121.4, and its multiple antibiotic resistance (MAR) index was detected to be 0.22. The tetL and aph(3')-IIIa were the most commonly found antibiotic resistance genes in the strains. However, E. mundtii strains HC56.3, HC73.1, HC147.1, and E. faecium strain HC121.4 were detected to lack any of the antibiotic resistance genes examined in this study. Only E. mundtii HC166.3 showed hemolytic activity, while none of the strains engage in gelatinase activity. The strains were identified to have virulence factor genes with a low rate. None of the virulence factor genes could be detected in E. mundtii HC26.1, HC56.3, HC73.1, HC165.3, HC166.8, and E. faecium HC121.4. The E. mundtii HC73.2 strain displayed the highest presence of virulence factor genes, namely gelE , efaA fs , cpd , and ccf . Similarly, the E. mundtii HC112.1 strain showed a significant presence of genes efaA fm , ccf , and acm . There was no decarboxylation of histidine, ornithine, or lysine seen in any of the strains. Nevertheless, E. faecium HC121.4 and HC161.1 strains could decarboxylate tyrosine, but E. mundtii HC26.1, HC56.3, HC73.1, HC73.2, HC112.1, HC147.1, HC155.2, HC165.3, HC166.3, HC166.5, and HC166.8 strains only showed a limited capacity for tyrosine decarboxylation. None of the strains possessed the hdc , odc , or ldc genes, but all of them had the tdc gene. Conclusion The E. mundtii HC56.3 and HC73.1 strains were deemed appropriate for utilization in food production. Using the remaining 11 strains as live cultures in food production activities could pose a possible risk to consumer health.